PUBLIC SERVICE COMPENSATION MECHANISM: LESSON FROM COMMUNITY HEALTH CENTERS PRACTICES - Laode Rudita; Asep Cahyana (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2026)
The fulfillment of the community's right to obtain decent health services and public facilities remains an unmet challenge for the government. The readiness of public health service providers to ensure all service recipient rights, as mandated by law, is relatively inadequate. As one unresolved policy issue in Indonesia, public service delivery is regarding provision of compensation to service recipients for service failure or unfulfilled service standards, it is also highly urgent for health service related to ensure patient safety dan convenience. However, the mandatory Presidential Regulation regarding public service compensation mechanisms, mandated more than a decade ago, has not yet been established, leaving service providers without implementation guidelines. Therefore, this study aims to explore the urgency, attributes, and “street-level practices” of compensation mechanism policies, particularly in public health services to realize healthy cities through quality public services. This research utilizes a qualitative approach involving descriptive, analytical, and socio-legal methods, gathering primary data through literature reviews, regulatory document analysis, and in-depth interviews with two of Community Health Center (CHC or Puskesmas) heads chosen purposively based on the result of Ombudsman Assesment of Compliance (Penilaian Kepatuhan) year 2023. The findings demonstrate significant good practices and policy initiations for providing compensation by the Puskesmas Kretek in Bantul Regency, Yogyakarta Special Region and the Puskesmas Kebondalem in Pemalang Regency, Central Java. These findings provide a foundational reference for broader national policy formulation of service compensation mechanism. Expecting adoption of the CHC’s compensation practices in national context, this study recommends for prioritizing compensation implementation in fully accredited health centers and outlines specific financial and non-financial compensation forms.